China and Albania: the Cultural Revolution and Cold War Relations. Issue 4 (2nd October 2017) - Marku, Ylber
Abstract: During the central decades of the Cold War, China was Albania's only ally. The aim of this article is to analyse how the Chinese Cultural Revolution affected Sino-Albanian relations. This article argues that the events in China threatened to undermine the Sino-Albanian alliance, because Albania did not endorse most of the Cultural Revolution's policies, but supported it only for the sake of relations with China and the benefits received from this alliance. In a time when the Cultural Revolution caused enormous difficulties to the Chinese economy, Albania nonetheless received an increasing amount of aid. Based on recently released archives, this case study sheds light on this underexplored Cold War alliance and adds to our understanding of how the Cultural Revolution had implications beyond China's borders.